GESTÃO DO CONHECIMENTO TÁCITO: ESTUDO DE CASOS MÚLTIPLOS NA ÁREA DE DESENVOLVIMENTO DE PRODUTOS DE EMPRESAS DO SETOR AUTOMOBILÍSTICO DO ABC PAULISTA. - GAVA, RENATA DE ALMEIDA VIANNA (2015)
This study aims to understand the reasons why the companies surveyed in the automotive sector to manage tacit knowledge, mediated by knowledge management in product development management. The research questions that this study aimed to answer was: How studied companies use tacit knowledge to become more efficient and effective in activities / operations? How tacit knowledge is perceived in the organization by employees and managers? To answer these questions was the investigation of two companies of the automotive sector in the product development area. As a theoretical basis for the development of the present study authors as Davenport and Prusak (1998), Nonaka and Takeuchi (1997) and Choo (2006) guide this research. The survey covers two companies in the automotive industry in the ABC Paulista region, with equivalence in the number of employees and size. Among the respondents there are employees and managers of projects and product management areas. The methodology applied to the study was qualitative through exploratory and descriptive research, and the data collection method is made from semi-structured interviews. The study investigated which practices used for the conversion of knowledge, facilitating factors and limiting factors for conversion of knowledge and major contributions to the application of practices and initiatives aimed manage tacit knowledge from the perspective of managers and employees. Through this study it can be seen that there is concern about knowledge management in the companies studied and there are several practices related to the tacit knowledge and forms of dissemination of this knowledge are different. Some of the practices are the specialization courses, brainstorming and lesson learned and informal conversations. In facilitating factors for the exchange of information among peers, weekly meetings, multidisciplinary / cross-functional teams. The hindering factors for the indication of behavioral issues, accumulation of functions and time to share information